2022
DOI: 10.3390/su14052849
|View full text |Cite
|
Sign up to set email alerts
|

Emotion or Information: What Makes Consumers Communicate about Sustainable Apparel Products on Social Media?

Abstract: This study investigated how sustainability-related messages of cotton textile and apparel products influence consumers’ attitudes toward the message and interaction with other consumers in social media. Three hundred and eighty-eight online survey data of US consumers investigated the effects of perceived information and emotion toward sustainability practice messages on attitude toward and social interaction with other consumers and the effects of attitude on social interaction in social media. The results co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Furthermore, the more stable the respondent's emotional response to the epidemic, the more positive the attitude, the more calmly they can look at other people's views on the epidemic and the reports of various media, and the stronger their willingness to participate in consuming behavior. The notion parallels the suggestion of Son et al that attitudes and subjective norms have a mediating effect in the process by which emotions influence purchase intentions [18]. Moreover, similar to our results, the finding of several studies suggested a positive relationship between emotional response, attitude, subjective norm, and intention [42,43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the more stable the respondent's emotional response to the epidemic, the more positive the attitude, the more calmly they can look at other people's views on the epidemic and the reports of various media, and the stronger their willingness to participate in consuming behavior. The notion parallels the suggestion of Son et al that attitudes and subjective norms have a mediating effect in the process by which emotions influence purchase intentions [18]. Moreover, similar to our results, the finding of several studies suggested a positive relationship between emotional response, attitude, subjective norm, and intention [42,43].…”
Section: Discussionsupporting
confidence: 92%
“…Consumers' purchasing behavior is affected by many factors, which is the process of generating corresponding consumer behavior willingness and consumer behavior to meet their own needs. Unlike scholars in China who focus on quality and safety perceptions [13,17], foreign scholars pay more attention to consumers' expected emotions [18,19]. The leading cause is that, although some scholars believe that attitude is one of the critical predictors in the theory of planned behavior, its predictive effect on behavior willingness has not achieved the expected outcome [20].…”
Section: Hypothesis 3 Perceived Behavior Control (Pbc) Positively And...mentioning
confidence: 99%
“…In this line, social advertising consists of an informative and, on many occasions, persuasive component, providing data likely to be remembered by the audience. The strategies for transmitting information can be different and may opt for (1) rational techniques that try to convince the viewer with data of impact and interest [48]; (2) emotional techniques that provoke the audience's sensitivity and empathy [49]; (3) high-impact techniques with aggressive images that attract the viewer's attention [50]; and (4) humorous techniques that capture the user and facilitate the transmission of information, although they may not be appropriate for some specific problems [51]. In addition to the communication strategy and the tone of the message, there are other formal variables that can influence the degree of recall and impact of a campaign or social news.…”
Section: Effectiveness Of Communication Campaigns For the Promotion O...mentioning
confidence: 99%
“…Several works consider indeed both the positive and the negative pole of emotional dimensions. For instance, Son et al. (2022) consider positive and negative emotions as “information” that contributes to develop positive or negative ATTs towards a behaviour and thus, to sustain or hinder its effective enactment.…”
Section: Literature Reviewmentioning
confidence: 99%